Soft Pressure Sensors - Integrated Into Compression Pressure Monitoring on Cardiopulmonary Resuscitation Device - Tran, Minh Ky; Ly, Thi Tuyet Nga; Nguyen, Bao Hy; Vu, Chi Cuong (Journal of Technical Education Science, 2025)
After more than a century of research and development, advancements in nanomaterials have led to significant breakthroughs, fostering innovation across various technological domains. Among these materials, graphene stands out as a pivotal advancement. The introduction of graphene has marked a transformative moment in the nanomaterials sector. Its unique properties and versatility have proven essential across various applications, including sensor fabrication and biomedical engineering. In this study, our research team utilized graphene-based conductive ink to fabricate force-sensing resistors (FSRs), capitalizing on graphene’s exceptional conductivity and adaptability. FSRs have garnered considerable interest from researchers due to their flexibility, cost-effectiveness, and favorable surface compatibility, making them ideal for wearable devices, health monitoring systems, and industrial applications. The sensors developed in this study demonstrated a high sensitivity to forces below 20N, with a sensitivity coefficient of approximately 0.9958N⁻¹. Additionally, they can withstand forces exceeding 100N, all while being only 1.01mm thick. This makes them suitable for a wide range of applications that require both high and low force measurements. The entirely manual fabrication process facilitates the customization of sensor properties to fulfill specific application demands. The sensor has been successfully integrated into CPR assistive devices for the measurement of applied force intensity and detection of force application location.